Measures of Core Inflation Used by the National Bank of Romania - Ionut - Cristian Baciu (CES Working Papers, 2015)
The inflationary process has become a phenomenon that has a significant influence on society in general and it is therefore important to be managed in an efficient manner. The objective of this study is to analyze the core inflation measures in Romania, after the adoption of direct inflation targeting regime in August 2005. In order to identify the causal link between the core inflation measures and inflation quantified by the Consumer Price Index (CPI), the Granger causality test is used. The study results indicate that only on the short-term the CORE 1 inflation (calculated using the Consumer Price Index from which the administered prices are eliminated) has influence on the total inflation, among the other core inflation measures and total inflation rate, the statistical relationships being insignificant.
Keywords: C22; E31; 330; core inflation; Consumer Price Index; Granger causality test